Ferramenta de Validação NCL: Aprimorando o processo de desenvolvimento de aplicações de TV Digital - Costa, Iago Victor Silva; Shuen, Li-Chang; Moraes, Daniel de Sousa; Santos, Joel André Ferreira dos; Muchaluat-Saade, Débora C.; Soares Neto, Carlos de Salles (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2024)
The Nested Context Language (NCL) is the declarative language of Ginga, the standard middleware of the Brazilian Digital Terrestrial TV System. From this perspective, the current paper presents an NCL Validation Tool, which presents code diagnostics through error or alert messages, aiming to ease the writing of software for Digital TV. The tool was evaluated using a script of activities with an evaluation scale ranging from 1 (the tool did not help) to 5 (the tool helped completely). Both during the analysis of the script results and the development of the tool, the usefulness of an assistant when authoring NCL applications became evident. Our preliminary results show that the proposed NCL Validation Tool can help productivity and learning of NCL.